Transfer of minimally manipulated CMV-specific T cells from stem cell or third-party donors to treat CMV infection after allo-HSCT - Neuenhahn, Michael; Schmitt, Michael (Leukemia, 2017)
Cytomegalovirus (CMV) infection is a common, potentially life-threatening complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT). We assessed prospectively the safety and efficacy of stem cell-donor- or third-party-donor-derived CMV-specific T cells for the treatment of persistent CMV infections after allo-HSCT in a phase I/IIa trial. Allo-HSCT patients with drug-refractory CMV infection and lacking virus-specific T cells were treated with a single dose of ex vivo major histocompatibility complex-Streptamer-isolated CMV epitope-specific donor T cells. Forty-four allo-HSCT patients receiving a T-cell-replete (D+ repl; n=28) or T-cell-depleted (D+ depl; n=16) graft from a CMV-seropositive donor were screened for CMV-specific T-cell immunity. Eight D+ depl recipients received adoptive T-cell therapy from their stem cell donor. CMV epitope-specific T cells were well supported and became detectable in all treated patients. Complete and partial virological response rates were 62.5% and 25%, respectively. Owing to longsome third-party donor (TPD) identification, only 8 of the 57 CMV patients transplanted from CMV-seronegative donors (D−) received antigen-specific T cells from partially human leukocyte antigen (HLA)-matched TPDs. In all but one, TPD-derived CMV-specific T cells remained undetectable. In summary, adoptive transfer correlated with functional virus-specific T-cell reconstitution in D+ depl patients. Suboptimal HLA match may counteract expansion of TPD-derived virus-specific T cells in D− patients.
Advance online publication, 17 February 2017
Gesehen am 28.06.2018